"If it ain't broke, don't fix it": a commentary on the positive-negative results of the ACCORD Lipid study - Tenenbaum Alexander; Fisman Enrique Z (Cardiovascular Diabetology, 2010)
Abstract Even using intensive statin monotherapy, many patients fail to achieve all the desired lipid goals and remain at high residual risk of cardiovascular events. In view of the still unproven decisively intensive "statin as monotherapy" strategy and "residual risk" concept, it is logical to ask whether other strategies, particularly fibrate/statin combination therapy, could be more beneficial and safer. A clear benefit of fibrate monotherapy did emerge previously among patients with atherogenic dyslipidemia (particularly high triglycerides and low high density lipoprotein cholesterol [HDL-C]) typically present in the metabolic syndrome and type 2 diabetes. In contrast, in patients without atherogenic dyslipidemia this favorable effect was not demonstrated. The Action to Control Cardiovascular Risk in Diabetes (ACCORD) study investigated whether combination therapy with a statin plus a fibrate, as compared with statin monotherapy, would reduce the risk of cardiovascular disease in patients with type 2 diabetes mellitus. However, relevant patients with atherogenic dyslipidemia represented less than 17 percent of the ACCORD Lipid population (941 out of 5518 patients). In this prespecified subgroup, the patients benefited from fenofibrate therapy in addition to simvastatin similar to the previous "fibrate's as monotherapy" trials: the primary outcome rate was 12.4% in the fenofibrate group, versus 17.3% in the placebo group (28% crude HR reduction, CI less than1, e.g. statistically significant findings). Among all other 4548 patients without atherogenic dyslipidemia such rates were 10.1% in both fenofibrate and placebo study groups. Authors concluded that in the overall cohort of patients the combination of fenofibrate and simvastatin did not reduce the rate of the cardiovascular events as compared with simvastatin alone. Thus, their results do not support the routine use of combination therapy with fenofibrate and simvastatin to reduce cardiovascular risk in the general patients with type 2 diabetes. A recent large meta-analysis regarding effects of fibrates on cardiovascular outcomes noted greater effect sizes in trials that recorded a higher mean baseline triglyceride concentration (p = 0.030). As expected, in a so called "general population", reflecting a blend of effects in patients with and without atherogenic dyslipidemia, a mean "diluted" effect of fibrate therapy was reduced, but still producing a significant 10% relative risk (RR) decrease in major cardiovascular events (p = 0.048) and a 13% RR reduction for coronary events (p < 0.0001). It should be pinpointed that the epidemiological characteristics of the ACCORD Lipid study depart from those seen in real clinical practice: among people with type 2 diabetes, there is a high prevalence of atherogenic dyslipidemia and metabolic syndrome. For example, an analysis of NHANES III data in adults aged ≥50 years showed that approximately 86% of patients with type 2 diabetes also had the metabolic syndrome. Therefore, an importand finding of ACCORD Lipid study was the observation that fibrates may lead to cardiovascular risk reduction in patients with atherogenic dyslipidemia not only as monotherapy but in combination with statins as well. In conclusion, in patients with atherogenic dyslipidemia (high triglycerides and low HDL-C, fibrates -- either as monotherapy or combined with statins - were associated with reduced risk of cardiovascular events. In patients without dyslipidemia this favorable effect - as expected - was absent.